Who is shaping the food choices of the future?. Issue 1 (13th February 2018) - Lockyer, S.
Abstract: A conference was held by the British Nutrition Foundation in October 2017 to explore future trends in agriculture, manufacturing and retailing, and the relationship between these trends and food choice. Topics explored by the speakers included sustainability, climate change, Brexit, the ageing population, technological advances in food production, product reformulation, consumer behaviour and public health agendas. This report summarises the conference proceedings.